2013
DOI: 10.5194/ms-4-167-2013
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of railway induced ground vibration through multibody and finite element modelling

Abstract: Abstract. The multibody approach is now recognized as a reliable and mature computer aided engineering tool. Namely, it is commonly used in industry for the design of road or railway vehicles. The paper presents a framework developed for predicting the vibrations induced by railway transportation. Firstly, the vehicle/track subsystem is simulated, on the basis of the home-made C++ library EasyDyn, by mixing the multibody model of the vehicle and the finite element model of the track, coupled to each other thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 28 publications
0
28
0
7
Order By: Relevance
“…In the theoretical analyses, the ground vibrations induced by moving train loads were mainly analyzed through trackÀ foundation models [1][2][3][4]. In the numerical simulation, the finite element method (FEM) [5][6][7][8], the boundary element method (BEM) [9,10], the combined FEMÀ BEM [11][12][13][14][15], and the combined FEMÀ IFEM (infinite element method) [16,17] were used to investigate the environmental vibration due to railway traffic. In the authors' previous study [18], highspeed train induced ground vibration was predicted with a trainÀ trackÀ ground system model, in which the vehicleÀ track coupled dynamics model [19] was applied to obtain the wheelÀrail dynamic forces and these forces were then used as the exciting loads inputted to the trackÀ ground system.…”
Section: Introductionmentioning
confidence: 99%
“…In the theoretical analyses, the ground vibrations induced by moving train loads were mainly analyzed through trackÀ foundation models [1][2][3][4]. In the numerical simulation, the finite element method (FEM) [5][6][7][8], the boundary element method (BEM) [9,10], the combined FEMÀ BEM [11][12][13][14][15], and the combined FEMÀ IFEM (infinite element method) [16,17] were used to investigate the environmental vibration due to railway traffic. In the authors' previous study [18], highspeed train induced ground vibration was predicted with a trainÀ trackÀ ground system model, in which the vehicleÀ track coupled dynamics model [19] was applied to obtain the wheelÀrail dynamic forces and these forces were then used as the exciting loads inputted to the trackÀ ground system.…”
Section: Introductionmentioning
confidence: 99%
“…e induced vibration may propagate through multiple paths. Kouroussis and Verlinden used a two-step approach to study ground vibration from subways [7], and this approach will also be used in the present paper. e system will be divided into two subsystems: the vehicle-tracktunnel rigid-flexible coupling subsystem (vibration generation) and the track-tunnel-soil three-dimensional finite element subsystem (vibration propagation), as shown in Figure 1(b).…”
Section: Establishment Of Prediction Modelsmentioning
confidence: 99%
“…Kouroussis and Verlinden built vehicle-track subsystem and tunnel-soil subsystem models using a two-step approach and developed a threedimensional ground vibration prediction model by coupling the two subsystems. To verify the prediction model, they measured the ground vibration caused by Brussels trains onsite [7,8]. Lopes predicted the source strength and the vibration received by surrounding buildings using a numerical method and adopted the method to research the vibration impact from subway operation and the induced vibration on houses.…”
Section: Introductionmentioning
confidence: 99%
“…which precludes the impact of forces outside a predefined distance range (recent numerical simulations showed that limited track part of 50-60 m length provides satisfactory results [23,24]). …”
Section: Problem Statementmentioning
confidence: 99%